1997
DOI: 10.1046/j.1365-2265.1997.2571066.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth hormone receptor by peripheral blood lymphocytes in children: evaluation in clinical conditions of impaired growth

Abstract: GH receptor expression on immune cells in non-syndromic short children appears to be inversely related to the linear growth expression and BMI of the subjects, contrary to findings with hepatic derived serum GHBP. This finding may reflect alternate exon usage in lymphoid cells, and indicates that GH has a distinctive role in the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Furthermore, mRNA expression of GHR, GHRtr, and their ratio showed no correlation with the donors' height SDS. This is consistent with previously reported results derived from peripheral blood lymphocytes [28]. The GHR/GHRtr ratio did not correlate with the absolute level of the two isoforms.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, mRNA expression of GHR, GHRtr, and their ratio showed no correlation with the donors' height SDS. This is consistent with previously reported results derived from peripheral blood lymphocytes [28]. The GHR/GHRtr ratio did not correlate with the absolute level of the two isoforms.…”
Section: Discussionsupporting
confidence: 93%
“…Aberrant GHR function may manifest as other traits related to GHR function in addition to prostate cancer risk. Both studies on mice and humans have reported changes in body mass and size with changes in the expressions of growth hormone and growth hormone receptor (13,(30)(31)(32), and genetic variation in other members of the growth hormone pathway have been implicated in BMI (33,34). We hypothesized that if the GHR haplotypes showing association with risk were truly involved in prostate cancer etiology, they may also bring changes in BMI (as it may be a surrogate marker for GHR expression levels).…”
Section: Discussionmentioning
confidence: 99%
“…Using flow cytometric analysis and immunofluorescence staining, GHR was shown to exist on B lymphocytes, T lymphocytes, natural killer cells and monocytes in human blood and the tonsil [10][11][12][13][14]. GHR expression was also shown in immune cells of other species: the PBMC, bone marrow, thymus, spleen and lymph node in rats [15][16][17] and bovine [18] (Table 1).…”
Section: Ghr In Immune Cellsmentioning
confidence: 99%